Sustainability Analysis of Black Soldier Fly Cultivation in Mojokerto City using Multidimensional Scaling-Rapfish - Lilis Sugiyarni; Nuhfil Hanani; Bunga Hidayati; Dini Atikawati; Nazilatul Azizah Mohd Radzi (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
Urban organic waste remains a major environmental challenge in developing cities worldwide. It constitutes the bulk of municipal waste streams, primarily the organic fraction, including household food waste and organic market scraps, and contributes significantly to greenhouse gas emissions. BSF larvae bioconversion offers a nature-based solution that can reduce organic waste while producing valuable biomass for circular bioresource systems. However, research that quantitatively evaluates the multidimensional sustainability of community-based BSF cultivation programs at the city level, particularly in Indonesia, is limited. This study evaluated the sustainability of the BSF cultivation program in Mojokerto City using MDS-RAPFISH, which encompasses five dimensions: environmental, economic, social, institutional, and technological. An indicator-based assessment utilizing conceptual modelling and policy analysis determined the program’s sustainability status and leverage attributes. The overall sustainability index was 54.22, which indicates moderate sustainability. The highest score was recorded in the environmental dimension (74.97). The subsequent dimensions were social (66.34), institutional (65.82), technological (61.70), and economic (60.92). These results show that there are constraints in terms of community participation, institutional support, technological consistency and market integration. The results show that although BSF cultivation has significant environmental benefits, it needs to be supported more technically and economically to be sustainable